STATUS LOGAM BERAT KADMIUM DAN HASIL RIMPANG TEMUIRENG (Curcuma aeruginosa Roxb.) PADA BEBERAPA DOSIS PEMUPUKAN FOSFAT - MONO RAHARDJO; ROSITA SMD; I. DARWATI (Jurnal Penelitian Tanaman Industri, 2000)
Status of cadmium and rhizome yield l/temuireng (Cur¬ cuma aeruginosa Roxb.) at by d fferent dosages phos¬ phatefertilizerCadmium is a heavy metal which is for human being. The concentration of Cd in the soil will increase if phosphate fertilizer is applied, because Cd is available in the sediment rock of phosphate as a raw material for phosphate fertilizer. Recently it is said that simplicia of medicinal crops originated from Asia is contaminated with heavy metals. That contamination mainly derives from Ihe environmental growth. Theefore, the research on the status of Cd in rhizomes Curcuma aeruginosa Roxb. due phosphate fertilizer is essential to be conducted. The experiment was conducted in the experimental garden of Research Institute for Spice and Medicinal Crops from August 1997 - June 1998. The experiment used polybags which were illed with 25 kg Bogor dry latosol soil mixed with I kg of rice husk and 2 kg cattle manue It used randomized block design (RBD) with four replications and ive samples each treatment. The treatments were (I) no NPK; and 8 dosages of TSP, (2)0; (3)2.5; (4)5; (5)7.5; (6)10.0; (7)12.5; (8)15.0; and (9)20.0g/ polybag respectively. Each TSP treatments was added with 1 5 g uea and 19 g KCI/ polybag. The plant wee harvested at 8.5 month after planting. The results of experiments showed that application of2.5; 5; 7.5; 10; 12.5; 15; and 20 g/polybag of TSP increased dry weight of simplicia from 24.3- 40%. The content of Cd in rhizomes, produced by plant with 5 up to 20 g TSP fertilizer was 1.181 - 2.756 ppm. The Cd content was higher than tolerance limited value as determined by laws of heavy metal in Japan (I ppm) and WHO (0.24 ppm). While fertilizer teatments of 0 and 2.5 g TSP produced rhizomes with Cd content 0.630 - 0.945 ppm, and it is still under tolerance limited value by Japan, but, higher than WHO laws. Due to high Cd content in rhizomes (1.181 - 2.756 ppm), those simplicia can not be used as row material for medicine.